Percepções sociolinguísticas interdialetais: o /S/ em coda silábica no português brasileiro - Henrique, Pedro Felipe de Lima (2023)
The main goal of this thesis is to investigate how listeners from different speech communities perceive, process, and evaluate alveolar and post-alveolar variants regarding the use of the postvocalic /S/ in the other's speech. For that, 240 Brazilian listeners between 18 and 30 years old from six Brazilian cities (Porto Alegre, São Paulo, Rio de Janeiro, Recife, João Pessoa, and Natal) took part in two perception tasks. In the first one, two distinct groups from each speech community listened to 32 recorded stimuli produced by Brazilian Portuguese speakers. 16 of those stimuli had alveolar or post-alveolar pronunciations of the post-vocalic /S/ produced by the same informant. The listeners judged the speakers based on positive and negative attributes, and after this evaluation, they had to indicate the speaker's city. The second test combined discrimination and an identification task. After completing the first task, the same judges had to show how different the two /S/ pronunciations sounded in the 16 pairs of recorded stimuli produced by another informant. These pairs were composed by a post-alveolar and an alveolar articulation. The degree of distinction was observed based on a point in a scale ranging from "totally equal" to "totally different", given to the listeners. After that, they had to choose which of the two pronunciations they perceived as prominent in their community and which was more commonly used by themselves. Among the main results regarding the discrimination experiment, we found that some linguistic variables, such as the voicing of the fricative and the position of the coda in the syllable, seem to influence the perception of the contrast between the pairs, regardless of the listener's speech community. On the categorization tests, we verified that the participants are aware of how their community behaves about the post-vocalic /S/, as the distribution patterns of the post-alveolar and alveolar variants found in production data correspond to the categorization patterns observed among the listeners considering their dialect of origin. In addition, they showed dialectal identification by the listeners concerning the variable, as the categorization patterns to adduce their townsman's way of speech corresponded to those selected for their own speech. About the results of the sociolinguistic perception tests, we detected a difference in the evaluation of the "accent" label among listeners from all speech communities, for whom speakers were perceived as having accent when listened to pronouncing post-alveolar fricatives. Among the listeners from Porto Alegre and Natal, the evaluation was higher among women than among men, and among those from João Pessoa, it was higher before the consonant [k]. When pronouncing post-alveolar fricatives, the speakers were judged by listeners from Porto Alegre as less reliable and less intelligent, by listeners from Recife as less smug, and by listeners from Natal and João Pessoa as funnier. Regarding the choice of cities to represent the origin of the speaker heard, we observed that listeners, especially those from the Northeast, have mainly chosen "Recife" to indicate the origin of speakers with post-alveolar pronunciations. At the same time, Rio de Janeiro was more chosen in these same conditions among listeners from the South and Southeast. São Paulo and Porto Alegre were most chosen when speakers pronounced alveolar fricatives, especially among listeners of these speech communities. The results reported here expand knowledge about fricatives in coda position in Brazilian Portuguese, spot the interdialectal recognition among Brazilian speakers and the indexicality related to their origin, and give some clues about possible social meanings linked to variants of this variable and its distributional and sociocognitive salience.